Pelatihan Literasi Teknologi: Pengembangan Kompetensi Dasar AI dan Coding Bagi Guru MGMP Matematika Rayon 1 Kota Jambi Sebagai Upaya Mendukung Program Kurikulum Deep Learning: (Technology Literacy Training: Developing Basic AI and Coding Competencies for Mathematics MGMP Teachers in Rayon 1, Jambi City, as an Effort to Support the Deep Learning Curriculum Program) - Anwar, Khairul; Kamid; kurniawan, Wawan; Anwar, Sofnidar; Pertiwi Rasmi, Dian; Anwar, Syaiful (Jurnal JUPEMA, 2026)
The rapid advancement of artificial intelligence (AI) and its integration into national curriculum policies demand that mathematics teachers acquire foundational competencies in both AI literacy and coding. However, the majority of in-service teachers lack structured training in these domains. This community service program provided technology literacy training for mathematics teachers of MGMP Rayon 1 Jambi City, focusing on developing AI and coding foundational competencies to support the Deep Learning Curriculum initiative. The program consisted of four stages: a diagnostic needs assessment, an intensive workshop covering AI fundamentals (prompt engineering, generative AI for lesson design) and block-based coding using Scratch and Python basics, a mentored classroom implementation phase, and a collaborative evaluation session. Pre- and post-assessments involving 35 teachers revealed that 91% of participants improved their AI literacy scores, with the average rising from 2.4 to 7.9 on a 10-point scale. In coding competency, 87% of participants successfully developed at least two functional mathematics learning projects. Classroom trials showed an 87% student engagement rate and an average 22.8% improvement in mathematical problem-solving scores. Additionally, 89% of teachers reported greater confidence in integrating AI tools and coding into daily instruction. These results demonstrate that a practice-oriented, context-responsive training model effectively prepares teachers for the demands of AI-era mathematics education. Abstrak. Kemajuan pesat kecerdasan buatan (AI) dan integrasinya dalam kebijakan kurikulum nasional menuntut guru matematika memiliki kompetensi dasar di bidang literasi AI dan coding. Namun, sebagian besar guru belum mendapatkan pelatihan terstruktur dalam kedua domain tersebut. Program pengabdian masyarakat ini menyelenggarakan pelatihan literasi teknologi bagi guru matematika MGMP Rayon 1 Kota Jambi, dengan fokus pada pengembangan kompetensi dasar AI dan coding untuk mendukung program Kurikulum Deep Learning. Program ini terdiri atas empat tahap: asesmen diagnostik kebutuhan, workshop intensif yang mencakup dasar-dasar AI (prompt engineering, AI generatif untuk desain pembelajaran) dan coding berbasis blok menggunakan Scratch serta dasar Python, fase implementasi terbimbing di kelas, dan sesi evaluasi kolaboratif. Penilaian sebelum dan sesudah pelatihan terhadap 35 guru menunjukkan bahwa 91% peserta meningkatkan skor literasi AI mereka, dengan rata-rata naik dari 2,4 menjadi 7,9 pada skala 10 poin. Dalam kompetensi coding, 87% peserta berhasil mengembangkan minimal dua proyek pembelajaran matematika fungsional. Uji coba di kelas menunjukkan tingkat keterlibatan siswa 87% dan peningkatan rata-rata 22,8% pada skor pemecahan masalah matematika. Selain itu, 89% guru melaporkan peningkatan kepercayaan diri dalam mengintegrasikan alat AI dan coding ke dalam pembelajaran sehari-hari. Hasil ini menunjukkan bahwa model pelatihan berbasis praktik dan responsif konteks secara efektif mempersiapkan guru menghadapi tuntutan pendidikan matematika di era AI.